ChemInform Abstract: Copper‐Catalyzed Selective Semihydrogenation of Terminal Alkynes with Hypophosphorous Acid. Issue 34 (26th August 2014) - Cao, Huanyang; Chen, Tieqiao; Zhou, Yongbo; Han, Daoqing; Yin, Shuang‐Feng; Han, Li‐Biao
Abstract The optimized conditions allow the selective semihydrogenation of a broad range of terminal aromatic and aliphatic alkynes to afford the corresponding alkenes in high yields.